PENGEMBANGAN KELEMBAGAAN TATA KELOLA HUTAN TAMAN NASIONAL GUNUNG HALIMUN SALAK - Neng Virly Apriliyani; Rita Rahmawati; Denny Hernawan (Jurnal Governansi, 2015)
This study aims to investigate the implementation of institutional development TNGHS forest governance, aspects of the advantages and disadvantages, and institutional design recommendations TNGHS Hall.               This study uses research is descriptive research method of analysis. This method is defined as a troubleshooting procedure investigated by describing the state of the subject or object of research that is going on at the present time based on the facts as they should be seen in the field               After analysis against each indicator of variable institutional development that the average score of respondents' assessment results is 3.84, which means being on the classification of Good assessment, thus assessment of the institutional development of  the national park forest governance Halimun Salak mountain has done well.               Although the classification assessment of all dimensions of institutional development are in the good category, but according to the results of interviews with respondents there are several dimensions that need to be improved further in the development of  institutional governance national park of halimun salak mountain bark like dimensions of resources, programs, link normative and link dispersed. Keywords: Institutional Development